Industrial collaborative robotics platform - Vicente, L. (2021)
Cyber-physical systems are not designed to integrate an industrial collaborative network when their integration with other systems is required. It is necessary to adopt a strategic model of integration and value creation that allows the interoperability of equipment supported by open technologies, based on the concepts underlying Industry 4.0. To this end, a conceptual information architecture is proposed to manage industrial robotic platforms based on a Cyber Device Bus design. The challenge is to contribute to an open technological framework involving computer systems, cyber-physical systems, and IoT elements in a logic of integration by adaptation without the need for specialized adapters. Adaptation occurs through the adoption of the informatics System of Systems (ISoS) technological framework, providing an integrated service-oriented (micro-services) view of technology elements and establishing cooperation between computer and cyber-physical systems under different responsibilities and based on a diversity of technological frameworks.